Entrepreneurship and economic growth - Audretsch, David B.; Keilbach, Max C.; Lehmann, Erik. (Oxford ; New York : Oxford University Press, 2006)
The book analyzes why entrpreneurship has emerged as an important economic force, and what the link is between entrepreneurship and economic growth. It also explains the emergence of new entrepreneurship policies. The authors make connections between entrepreneurship and economic growthat the levels of individual firms and entire regions.
Includes bibliographical references (p. 199-217) and index.
oif 18/07/14
Loan
Keywords: Entrepreneurship; Creative ability in business; Small business; Technological innovations; Diffusion of innovations; Economic development